Pengaruh Latihan Variation Of Body Drops Dan Metode Latihan Pull Up Dalam Meningkatkan Kecepatan Pukulan Gyaku Tsuki Chudan Pada Atlet Kumite Perguruan Kknsi Dojo Don Bosco Diski Tahun 2022 - Banjarnahor, Petra Yohana; Nurkadri; Rahma Dewi; Sitepu, Indra Darma; Iway Akbar; Abdul Fattah Zaidan (Jurnal Ilmiah STOK Bina Guna Medan, 2025)
This study aims to determine the effect of variation of body drops training and pull up training methods in increasing the speed of gyaku tsuki chudan punches in Kumite athletes at the 2022 KKNSI Dojo Don Bosco Diski School. This study uses an experimental method with a one group pre-test post-test design. In this study, the population was all Dojo Don Bosco Diski karate athletes. The sampling in this study was carried out by purposive sampling (conditional sampling). After providing several requirements, a research sample of 12 athletes could be drawn. The data collection technique used was by taking a pre-test and post-test. From the data analysis that has been carried out, it is known that the t_count value of the hypothesis is obtained at 7.272 and t_table 1.795, so (t_count 7.272 > t_table 1.795), so there is a significant influence of variation of body drops training and pull up training methods in increasing the speed of gyaku tsuki chudan punches in Kumite athletes at the Don Bosco Diski Dojo KKNSI School in 2022. Therefore, it can be concluded that the combination of both training methods is effective in enhancing the punch speed performance of Kumite athletes.